2021
DOI: 10.1088/1742-6596/1793/1/012038
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Asphalt Pavement Cracks using mobile 2D laser scanning system: A case study of UTM 30LX laser scanner

Abstract: For road construction, cracking is the main factor affecting pavement damage, which can decrease the quality of pavement and seriously affect transportation. To ensure the quality of the road surface for safety transportation, it needs to check the status of the road surface periodically. Structural health monitoring solutions, such as strain gauges and fiber optics systems, have been proposed for the monitoring of such cracks. However, expensive devices prevent these solutions being deployed. In this study, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Some provided results for URG-04LX have been summarized in Table 9 [ 19 , 22 ]. Similarly, the scanning results for UTM-30LX have listed in Table 9 for different research works and no unique observation has been observed as stated in related articles [ 28 , 29 , 40 ].…”
Section: Characteristics Of Laser Scanners In Indoor Environmentmentioning
confidence: 81%
See 1 more Smart Citation
“…Some provided results for URG-04LX have been summarized in Table 9 [ 19 , 22 ]. Similarly, the scanning results for UTM-30LX have listed in Table 9 for different research works and no unique observation has been observed as stated in related articles [ 28 , 29 , 40 ].…”
Section: Characteristics Of Laser Scanners In Indoor Environmentmentioning
confidence: 81%
“…results for UTM-30LX have listed in Table 9 for different research works and no unique observation has been observed as stated in related articles [28,29,40].…”
Section: Plos Onementioning
confidence: 87%
“…In detail, the x-axis is parallel to the slider and points to the movement direction; the zaxis is perpendicular to the scanning plane. Its positive direction coincides with gravity, and the right-hand rule determines the y-axis [24]. erefore, the coordinates of the points in the point cloud can be calculated using the following equation:…”
Section: Point Cloud Generation Data Processing Includes Many Stepsmentioning
confidence: 99%